The scarce representation of women university professors in research groups - María José Rodríguez-Baiget; Alexander Maz Machado; José Carlos Casas del Rosal; Arnaldo Vergara-Romero (Institute of Advanced Engineering and Science, 2024)
Women university teachers in Spain simultaneously have teaching and research careers that interrelate to develop their competencies in both fields. However, as in other fields, there is not yet gender equality in representation and leadership. This paper presents a descriptive analysis of the presence and role of female university teachers-researchers in the different research groups of public universities in the Autonomous Community of Andalusia that apply for competitive calls for projects, according to the different fields of knowledge to which they belong. A total of 2,445 research groups in nine universities were identified. The largest number of groups belonging to the Humanities field. Among the members of all the groups, there is a lower presence of women compared to men. There is also a negative gender gap in the roles of responsibility and management of research groups, which is reflected in both horizontal and vertical segregation and the existence of a glass ceiling for Andalusian female teachers.